Efficacy of microneedling with PDRN salmon 3% to reduce facial hyperpigmentation: skin hyperpigmentation index (SHI) analysis - Vera, Vera; I Gusti Ayu Agung Praharsini (Aesthetic Medicine, 2025)
Aim: The study aimed to assess the safety and efficacy of microneedling (MN) combined with Polydeoxyribonucleotide (PDRN) Salmon 3% for treating facial hyperpigmentation.Methods: Two patients, aged 40 and 50, underwent two MN sessions combined with PDRN 3%, spaced 3 weeks apart. Photos were taken before and after each visit, as well as at the final visit (6 weeks after baseline).Results: Photos were analyzed through a Skin Hyperpigmentation Index (SHI) analysis. Both patients showed improved skin quality, brighter facial skin, and reduced facial hyperpigmentation based on SHI scores. No side effects were noted during or after treatment.Conclusion: Combined therapy of MN and PDRN 3% shows promising outcomes in improving skin quality and hyperpigmentation. To the best of the author’s knowledge, these are the first reported cases of MN combined with PDRN 3% for reducing hyperpigmentation.